Effects of briakinumab treatment for moderate to severe psoriasis on health‐related quality of life and work productivity and activity impairment: results from a randomized phase III study. (17th May 2013) - Papp, K.A.; Sundaram, M.; Bao, Y.; Williams, D.A.; Gu, Y.; Signorovitch, J.E.; Wang, Y.; Valdes, J.M.; Mulani, P.M.
Abstract Background Psoriasis is known to have a significant negative impact on a patient's health‐related quality of life, including social, recreational and work activities. Objective To evaluate the effects of briakinumab on quality of life and work productivity measures in patients with moderate to severe psoriasis. Methods Patients received either briakinumab (n = 981) or placebo (n = 484) during the 12‐week induction phase of trial M06‐890. At week 12, patients with a Physician's Global Assessment score of 'Clear' or 'Minimal' entered the 40‐week maintenance phase and were to receive briakinumab every 4 weeks, briakinumab every 12 weeks, or placebo. At weeks 12 and 52, treatment groups were compared using mean change from baseline in health‐related quality of life and Work Productivity and Activity Impairment Questionnaire scores and the percentage of patients with minimum clinically important differences. Results At week 12, more than half of the briakinumab‐treated patients achieved improvements meeting or exceeding minimum clinically important differences for Dermatology Life Quality Index (75.9%), and psoriasis‐ (64.8%), and psoriatic arthritis‐related (54.1%) pain scores; 48.4% achieved improvements for activity impairment. Although improvements in quality of life and work productivity measures were maintained at week 52 for both briakinumab regimens, responder rates were consistently greater in the every‐4‐week group than in the every‐12‐week group. Conclusion Briakinumab treatment resulted in clinically significant improvements in quality of life and work productivity in adults with moderate to severe psoriasis. Maintenance therapy was associated with a more pronounced benefit for the every‐4‐week briakinumab regimen.